The $k$-Lucas Hyperbolic Functions - Taşçı, Dursun; Azman, Huriye (Communications in Mathematics and Applications, 2014)
In this paper, we introduced and studied an extension of the classical hyperbolic functions. We de…ned $k$-Lucas hyperbolic functions and studied their hyperbolic and recurrence properties, and investigated the relations between this new $k$-Lucas hyperbolic functions and the $k$-Fibonacci hyperbolic functions, which were studied before by Falcon and Plaza. We also studied the quasi-sine $k$-Lucas functions.